FEATURES OF EMPLOYMENT OF FOREIGN CITIZENS IN THE RUSSIAN FEDERATION - T. Suvalova (Вестник университета, 2017)
The article examines the particulars of the work and procedure of employment of citizens from other States. Therefore, classification of foreign citizens, the law clarifies the status of foreigners and established rules of stay on the territory of the Russian Federation. Marked by severe restrictions of the rights of foreign citizens to engage in certain activities and rights to occupy certain positions. The article focuses on the liability of employers for employment of illegal immigrants.